Teaching methodologies in a weekend madrasah: a study at Jamiyah Education Centre, Singapore - Rustam, Nora; Mamat, Arifin; Abdul Rashid, Adnan (Center for Enhancing Knowledge, United Kingdom, 2012)
Jamiyah Singapore is a non-profit organization that aims to provide service to humanity by promoting missionary, education and welfare. Jamiyah Education Centre (JEC) is one of the organization’s pioneering project since 1970s. JEC provides Islamic education to all Muslims in Singapore ranging from pre-schoolers to adults. This study investigated the teaching and learning process of Islamic education in Jamiyah Education Centre (JEC). Specifically, it examined the teaching methodologies that are mostly used by the Islamic education teachers; the most preferred methodologies from the students’ perspectives and the level of effectiveness of attending the weekend Madrasah that attracts students’ participation in class and eventually contributes to their personality development. The survey method was employed in this study and three hundreds and two (302) students are the sample. The study also used a set of questionnaire for students to gather the data. Meanwhile the descriptive statistics were used for the data analysis. This study revealed that, the teaching methodologies that are frequently employed by the JEC teachers is, the method of lecture. The results also indicated that the most preferred teaching strategy by the students is the use of humor. Finally and most importantly, the finding has proven that students found the programme to be highly effective and eventually it has made them a better person.